The Organization of Clinical Trials for Oncology at IRCCS Istituto Nazionale Tumori "Fondazione G. Pascale" Napoli and the Impact of the OECI Accreditation Process. (December 2015) - De Feo, Gianfranco; D'Ambrosio, Francesca; Palmieri, Giada; Perrone, Francesco; Ciliberto, Gennaro
The Istituto di Ricovero e Cura a Carattere Scientifico (IRCCS) Istituto Nazionale Tumori "Fondazione G. Pascale" (INT-Pascale) is the largest Clinical Care and Research Cancer Center in Southern Italy. The mission is prevention, diagnosis, and care of cancer and innovative research in oncology. In 2013, INT-Pascale joined the Organisation of European Cancer Institutes (OECI) accreditation and classification project along with other Italian IRCCS cancer centers. One of the major OECI requirements that a cancer center must fulfill in order to achieve and maintain OECI certification is a strong emphasis in translational and clinical research: increasing the number of patients enrolled in clinical trials, establishing easily accessible databases for operators, and informing all possible stakeholders, including patients. A characterizing theme of INT-Pascale is a strong commitment to clinical experimental studies. In the 2007-2014 period, 440 clinical trials were activated at INT-Pascale; in this period, the number of clinical trials and observational studies has had an increment achieving in 2014, respectively, the share of 60 clinical trials and 35 observational studies activated. Optimization of clinical trials management and dissemination of the clinical research culture at INT-Pascale are main objectives to be achieved through several actions and procedures being implemented as a component of the OECI improvement plan. Participation in the OECI program has represented an important challenge to improve quality and processes related to promoting, prioritizing, and monitoring clinical trials at INT-Pascale.